Studi Simulasi Pengaruh dari Pitch dan Kecepatan Alir Fluida Kerja Terhadap Koefisien Perpindahan Panas Menyeluruh di Conical Cavity Absorber - Jusva Agus Muslim; Laode M Firman (Magister Teknik Mesin Universitas Pancasila, 2020)
The energy crisis has become a global issue that must be resolved immediately through the use of new and renewable energy sources. Indonesia is geographically benefited because it is on the equator so that it gets a supply of sun throughout the year. This advantage is an added value for the application of solar-based energy systems. Concentrated Solar Power (CSP) system is an energy system based on solar thermal energy to generate electricity. The parabolic dish model in CSP has been shown to have the highest efficiency of up to 32%. The fundamental challenge of improving performance on the parabolic dish model is the design of the cavity receiver used. Cavity receiver functions to absorb heat from the reflector and distribute it to the system through the working fluid (Heat Transfer Fluid). This article specifically discusses the simulation of conical cavity receivers with a focus on the effect of pitch and fluid flow velocity in the system through Computational Fluid Dynamic (CFD) ANSYS. Simulation results on nine different variables show the effect of pitch and flow velocity on the overall transfer coefficient on cavity. The results of this simulation can be used as a basic reference in an effort to improve the heat transfer performance of cavity, which in turn can affect the overall performance of a Concentrated Solar Power Parabolic Dish type system.